Pedagogical Strategies for Teaching Virtual Production Pipelines - Bennett, Gregory; Najafi, Hossein; Jackson, Lee (ACM, 2023)
The incorporation of LED walls and virtual production tools in the film industry is a recent development that has significant pedagogical implications (BLISTEIN, 2020; FARID and TORRALBA, 2021). The use of LED walls combines physical and digital realities, potentially reducing post-production time and resource usage (ONG, 2020). Virtual production can facilitate immediate on-set decision-making and mitigate the need for certain post-production adjustments (EPIC GAMES, 2020). MIT researchers posit that such practices may also reduce the carbon footprint associated with location filming (FARID and TORRALBA, 2021). Nonetheless, further research and innovation are needed to overcome any limitations and fully harness the potential of this technology. The utilization of Unreal Engine software and other real-time tools in visual effects education aligns with industry trends and enhances student preparedness for professional practice (FLEISCHER, 2020). It has been suggested that engaging students with these tools can foster an understanding of the virtual production pipeline, thus aligning the educational curriculum with evolving industry standards (BALSAMO et al., 2021). As educators at Auckland University of Technology, we recognized the necessity of early integration of these paradigm-shifting tools into our curriculum to prepare students for impending and ongoing industry changes. In anticipation of procuring LED walls, we explored the potential of leveraging existing resources to initiate a pedagogical foray into the virtual production sphere. The available resources encompassed a large green screen studio, a motion capture studio, and virtual reality (VR) headsets and trackers. This paper offers two pedagogical responses that were deployed in courses situated in the final (third) year of undergraduate studies for an Animation, Visual Effects and Game Design Major, Bachelor of Design, at the School of Art and Design, Auckland University of Technology. One course is positioned within a motion capture minor and the other an option within a major capstone project framework. These two responses form case studies in the technical modification of existing teaching equipment and the need to push the limits of existing software and hardware resources within the attendant budgetary constraints of a tertiary education institution. This, in turn, is in the service of meeting shifting tertiary curriculum demands in response to a technologically fluid and future-focused industry.